2021
DOI: 10.1038/s41598-021-01549-z
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus spike protein ΔVP8* as a novel carrier protein for conjugate vaccine platform with demonstrated antigenic potential for use as bivalent vaccine

Abstract: Conjugate vaccine platform is a promising strategy to overcome the poor immunogenicity of bacterial polysaccharide antigens in infants and children. A carrier protein in conjugate vaccines works not only as an immune stimulator to polysaccharide, but also as an immunogen; with the latter generally not considered as a measured outcome in real world. Here, we probed the potential of a conjugate vaccine platform to induce enhanced immunogenicity of a truncated rotavirus spike protein ΔVP8*. ΔVP8* was covalently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…To investigate the feasibility of using RV as an expression vector, we analyzed the effect of introducing SARS-CoV-2 spike peptides into the “head” region of the VP4 (i.e., VP8* domain), outside the sialic acid binding domain. Since VP8* is used in several vaccine platforms such as protein subunit or nanoparticle vaccines to induce RV-specific neutralizing antibodies ( 73 78 ), we hypothesized that the expression of SARS-CoV-2 spike peptides by VP8* may similarly generate neutralizing antibodies. However, incorporation of various spike epitopes into the VP8* lectin domain between amino acid positions 164 to 198 consistently showed significant decrease in viral titers, despite having no obvious effect on the rescue efficiency ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the feasibility of using RV as an expression vector, we analyzed the effect of introducing SARS-CoV-2 spike peptides into the “head” region of the VP4 (i.e., VP8* domain), outside the sialic acid binding domain. Since VP8* is used in several vaccine platforms such as protein subunit or nanoparticle vaccines to induce RV-specific neutralizing antibodies ( 73 78 ), we hypothesized that the expression of SARS-CoV-2 spike peptides by VP8* may similarly generate neutralizing antibodies. However, incorporation of various spike epitopes into the VP8* lectin domain between amino acid positions 164 to 198 consistently showed significant decrease in viral titers, despite having no obvious effect on the rescue efficiency ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging virus strains have been associated with mutations that render vaccines and other therapies, such as monoclonal antibodies, less effective as seen with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Starr et al 2021). Previous studies have shown that the VP5* and VP8* outer capsid proteins play a significant role in inducing neutralising antibodies against rotaviruses (Ludert et al 2002; Park et al 2021; Ruggeri and Greenberg 1991; Zhao et al 2015). The VP5* protein of the Malawian G3P[8] strains were 100% conserved when compared to that of Rotarix vaccine, consistent with previous studies that have reported that the VP5* is a highly conserved protein (Rasebotsa et al 2020; Mwangi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…VP8* domain), outside the sialic acid binding domain. Since VP8* is used in several vaccine platforms such as protein subunit or nanoparticle vaccines to induce RV-specific neutralising antibodies [81][82][83][84][85][86], we hypothesised that the expression of SARS-CoV-2 spike peptides by VP8* may similarly generate neutralising antibodies. However, incorporation of various spike epitopes into the VP8* lectin domain between amino acid positions 164 -198 consistently showed significant decrease in viral titres, despite having no obvious effect on the rescue efficiency (Fig.…”
Section: Discussionmentioning
confidence: 99%